Effective DNA fragmentation technique for simple sequence repeat detection with a microsatellite-enriched library and high-throughput sequencing - Keisuke Tanaka; Rumi Ohtake; Saki Yoshida; Takashi Shinohara (BioTechniques)
Two different techniques for genomic DNA fragmentation before microsatellite-enriched library construction—restriction enzyme (NlaIII and MseI) digestion and sonication—were compared to examine their effects on simple sequence repeat (SSR) detection using high-throughput sequencing. Tens of thousands of SSR regions from 5 species of the plant family Myrtaceae were detected when the output of individual samples was >1 million paired-end reads. Comparison of the two DNA fragmentation techniques showed that restriction enzyme digestion was superior to sonication for identification of heterozygous genotypes, whereas sonication was superior for detection of various SSR flanking regions with both species-specific and common characteristics. Therefore, choosing the most suitable DNA fragmentation method depends on the type of analysis that is planned.